2007
DOI: 10.1136/thx.2006.065540
|View full text |Cite
|
Sign up to set email alerts
|

Six-minute walking versus shuttle walking: responsiveness to bronchodilation in chronic obstructive pulmonary disease

Abstract: Background: The responsiveness of the endurance shuttle walk to functional changes following bronchodilation has recently been reported. The current literature suggests that the 6 min walking test (6MWT) is less responsive to bronchodilation than the endurance shuttle walk. Aim: To compare bronchodilator-induced changes in exercise performance with the 6MWT and the endurance shuttle walk. Methods: In a randomised, double-blind, placebo-controlled, crossover trial, 14 patients with chronic obstructive pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
3
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(172 citation statements)
references
References 34 publications
8
156
3
5
Order By: Relevance
“…This is probably due to the differences between these two exercise modalities. In comparison with cycling, walking has been shown to be less fatiguing and to produce less lactate at similar V9O 2 levels [19][20][21]. Hence, patients are able to exercise for longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the differences between these two exercise modalities. In comparison with cycling, walking has been shown to be less fatiguing and to produce less lactate at similar V9O 2 levels [19][20][21]. Hence, patients are able to exercise for longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…The randomness of this variability suggests that it was not related to a learning effect, as confirmed by the Bland-Altman plot. The issue about intraindividual variability in exercise performance was previously discussed for the ESWT [12,[19][20][21], but also for constant work-rate cycling exercise [22]. REVILL et al [21] reported greater variability in ESWT performance with longer endurance time.…”
Section: Reproducibility Of Eswt Performancementioning
confidence: 99%
“…As such, measuring the endurance to constant load exercise has been an important objective of several clinical trials evaluating the impact of pharmacological or rehabilitative interventions in COPD [3][4][5]. In this context, the endurance shuttle walking test (ESWT) is gaining acceptance due to its minimal requirement for equipment, low cost and ease of administration [6], and to its responsiveness and sensitivity to interventions, at least in single centre studies [7][8][9][10][11][12]. With the advancement of portable cardiopulmonary monitoring, it is also possible to obtain a thorough physiological assessment during the ESWT.…”
Section: Introductionmentioning
confidence: 99%
“…A large rehabilitation study reported mean changes of 75.9 m [281]. In a large group of patients with COPD, the SWT was sensitive to the administration of formoterol and ipratopium bromide [283,284]. The endurance SWT (ESWT) seems more sensitive to change after a course of rehabilitation than the ISWT.…”
Section: Walking Testsmentioning
confidence: 99%